ERROR ANALYSIS OF ENGLISH WRITTEN ESSAY OF HIGHER EFL LEARNERS: A CASE STUDY - Rina Husnaini Febriyanti; Hanna Sundari (Journal of English Language Studies, 2016)
The aim of the research is to identify grammatical error and to investigate the most and the least of grammatical error occurred on the students’ English written essay. The approach of research is qualitative descriptive with descriptive analysis. The samples were taken from the essays made by 34 students in writing class. The findings resulted in: the most common error occurred was subject-verb agreement error and the score was 28, 25%. The second place of frequent error was on verb tense and form with 24, 66% as the score. The third was on spellings errors and the value is 17, 94%. The fourth was error on using auxiliaries and the score 9, 87%. The fifth was error on word order with the score was 8.07%. The rest error was applying passive voice with the score is 4.93%, articles (3.59%), prepositions (1.79%), and pronoun and run-on sentence with the same scores, 0. 45%. This may indicate that most students still made errors even for the usage of basic grammar rules in their writing. Keywords: developing essay; grammatical error; writing